SERIES ECONOMICS APPLIED TO ENGINEERING PROCESS ( PART 4 ​​) CONTROL FACILITY MANAGEMENT RESPONSIBILITY : DIRECT AND INDIRECT COSTS COSTS . - Leyva C., Máximo (2005)
The companies are engaged in maximizing their wealth or economic growth. So how systems require evaluating the management of its management noting that assume authority and responsibility in the incurrence of costs and revenues . In this fourth edition intends to consolidate the concepts of costs associated with the methodologies of evaluating the performance of responsibility centers ( CR ) , which will require to process engineers in the industry to have a deep understanding of the fundamental concepts of behavior cost and higher capacity proposals to implement improvement plans in general.